Soft and breathable EVA insole and preparation method thereof
By using specific raw materials combinations in EVA insoles to form microporous structures and pore networks, the problems of insufficient breathability and humidity removal of EVA insoles are solved, and their performance in high-strength and high-humidity environments are significantly improved.
Patent Information
- Application Number
- CN202411649757.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lack of breathability and moisture removal of EVA insoles leads to stuffy and hot feet, increasing discomfort, and may induce skin health problems, and perform poorly in high-intensity and high humidity environments.
The use of raw materials such as ethylene-vinyl acetate copolymer, activated carbon, porous silica, chitosan, end-epoxy polyether silicone oil, modified starch, cellulose and polyacrylamide to form microporous structures and pores through synergistic action. Network to improve breathable and humidity exhaust performance.
It significantly improves the breathability, moisture removal, softness, strength and durability of EVA insoles, making it suitable for use in high-strength and high-humidity environments.
Smart Images

Figure BDA0005140594210000051 
Figure BDA0005140594210000061 
Figure BDA0005140594210000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of EVA insole processing, and more specifically, to a soft and breathable EVA insole and a preparation method thereof. Background Art
[0002] EVA insoles are made of ethylene-vinyl acetate copolymer as the main material. They have excellent softness, elasticity, impact resistance, water and moisture resistance, and heat insulation. However, due to the tight molecular structure of EVA materials, air and moisture are difficult to penetrate, and there are problems with insufficient air permeability and moisture discharge. Long-term wearing of such insoles can easily cause the foot environment to be stuffy, increase discomfort, and promote bacterial growth due to sweat accumulation, which can induce skin health problems such as athlete's foot and itchy feet.
[0003] In order to further improve the air permeability and moisture removal of EVA insoles, a foaming agent is usually added. The foaming agent can trigger a chemical reaction under heating or specific conditions, thereby forming a uniformly distributed micropore or pore network inside the EVA material. These microstructures not only serve as channels for gas exchange, enhancing the air permeability and moisture removal capacity of the insole, but also help regulate the microclimate of the foot and reduce moisture accumulation. However, in the process of using the foaming agent, the amount of the foaming agent needs to be strictly controlled, and its amount becomes the key to balancing the air permeability and material structural integrity. If the amount of foaming agent is too much, the air permeability and moisture removal performance will be greatly increased. However, too much pore structure will weaken the overall structure of the insole, reduce its ability to withstand external forces, and cause the softness, compressive strength and durability of the EVA insole to decrease, affecting the stability and comfort of long-term use; too little foaming agent will lead to a decrease in the air permeability and moisture removal performance of the EVA insole.
[0004] Therefore, in the process of preparing EVA insoles, the amount of foaming agent is generally 5-10% of the total amount. By adding 5-10% of foaming agent, the air permeability and moisture removal performance of the EVA insole can be greatly improved, and the EVA insole also has a certain softness and strength. However, in actual use, it is found that although the EVA insole with 5-10% foaming agent can meet the general daily wear needs, its comprehensive performance of air permeability and moisture removal, softness, strength and durability is still insufficient in high-intensity and high-humidity environments (such as mountaineering, long-distance running and other activities). Summary of the invention
[0005] In order to further improve the air permeability, moisture discharge, softness, strength and durability of the EVA insole, the present application provides a soft and breathable EVA insole and a preparation method thereof.
[0006] In a first aspect, the present application provides a soft and breathable EVA insole, which adopts the following technical solution: A soft and breathable EVA insole is prepared from the following raw materials in percentage by weight: Ethylene-vinyl acetate copolymer 40-52% Activated carbon 4-8% Porous silica 15-20% Chitosan 5-8% Epoxy-terminated polyether silicone oil 4-6% Modified starch 5-9% Cellulose 3-6% The remainder is polyacrylamide.
[0007] By adopting the above technical solution and through the synergistic effect of various raw materials, the breathability, moisture removal, softness, strength and durability of the EVA insole can be fully optimized, making it more suitable for use in high-intensity and high-humidity environments such as mountaineering and long-distance running.
[0008] By utilizing the high specific surface area and porous structure of activated carbon and porous silica, the porous structure provides channels for the circulation of gas and moisture, allowing the air and moisture inside the insole to be exchanged smoothly, thereby improving breathability and moisture discharge, keeping the feet dry and comfortable even during long-term high-intensity activities and reducing bacterial growth.
[0009] The epoxy-terminated polyether silicone oil can penetrate into the EVA substrate, increasing the flexibility of its molecular chain, making the insole have a better soft touch while maintaining sufficient support, improving the fit and comfort of wearing. At the same time, it forms a three-dimensional network structure with ethylene-vinyl acetate copolymer, enhancing the cohesion and tensile strength of the material, and improving the wear resistance and deformation resistance of the insole. The introduction of natural polymer materials such as chitosan, modified starch and cellulose forms good compatibility with ethylene-vinyl acetate copolymer, giving the insole a softer feel and elasticity, and improving the comfort of wearing.
[0010] Polyacrylamide not only plays the role of filling and reducing costs, but also enhances the overall structural stability of the insole through its intermolecular interactions, preventing the material from loosening and falling off during use.
[0011] Preferably, the modified starch is prepared by the following method: A: Mix polylactic acid and solvent and stir, raise the temperature to 75-80°C until the polylactic acid is completely dissolved to obtain a polylactic acid solution; B: Stir starch, ammonium sulfate and water, heat to 75-80°C, and stir until the starch becomes transparent to obtain gelatinized starch; C: Mix polylactic acid solution, gelatinized starch and maleic anhydride, heat to 90-100°C, add ammonium bisulfite solution dropwise, keep warm for 1-2 hours after the addition is complete, then cool to 50-60°C, continue heating and stirring for 1-1.5 hours, add 4-methylimidazole and stir until the temperature drops below 40°C, adjust the pH value to 7-7.5 with ammonia water, and obtain modified starch.
[0012] By adopting the above technical scheme, the modified starch prepared can further improve the softness and air permeability of EVA insoles, and the polylactic acid in the modified starch forms good compatibility with the EVA molecular chain, which increases the flexibility between molecules, so that the insoles can better disperse the pressure when stressed, and improve the comfort of wearing. At the same time, the good compatibility of the modified starch and the EVA substrate helps to maintain the uniformity of the insole structure, avoids pore blockage, and is indirectly conducive to the maintenance of air permeability. In addition, the polylactic acid and maleic anhydride reactants in the modified starch enhance the interaction between starch and the EVA substrate, improve the overall strength of the composite material, and make the insole difficult to deform or break during long-term use, and extend the service life.
[0013] Among them, lactic acid is dissolved in the solvent to form a uniform solution, and starch is heated and gelatinized under the action of ammonium sulfate and water to form gelatinized starch with fluidity. These two steps provide the reactant basis for subsequent reactions. After the lactic acid solution, gelatinized starch and maleic anhydride are mixed, maleic anhydride promotes the grafting reaction between polylactic acid and starch molecules, while the addition of ammonium bisulfite solution and the heat preservation reaction further promote the grafting process, forming a modified starch with new properties. At the same time, by adding 4-methylimidazole and adjusting the pH value, the reaction end point can be controlled and the structure of the modified starch can be stabilized.
[0014] Preferably, the weight parts of the raw materials used to prepare the modified starch are as follows: Polylactic acid 4-8 parts Solvent 10-15 parts 10-15 parts starch 1-2 parts ammonium sulfate 18-22 parts water Maleic anhydride 1.5-3 parts 3-4 parts of ammonium bisulfite solution 1-2 parts of 4-methylimidazole 3-5 parts of ammonia water; The ammonium bisulfite solution is obtained by mixing ammonium bisulfite and water in a weight ratio of 1:(4-5).
[0015] By adopting the above technical scheme, the amount of raw material for preparing modified starch is optimized, and the grafting rate of polylactic acid and starch is further improved, so that the compatibility of modified starch and EVA matrix is better, thereby obtaining EVA insoles with better air permeability, softness and strength.
[0016] Preferably, the porous silica has a pore size of 20-50 nm and an average particle size of 200-800 nm.
[0017] By adopting the above technical solution, the pore size and average particle size of porous silica are optimized, and the microporous structure of the EVA insole is increased, which helps the gas exchange inside the insole, so that the insole can more effectively discharge moisture and heat while maintaining its softness, reduce the feeling of stuffiness in the feet, and improve the comfort of wearing. At the same time, nano-scale silica can increase the strength of the EVA insole mesh structure and improve the durability of the insole.
[0018] Preferably, the pore size of the activated carbon is 50-100 nm, and the average particle size is 500-900 nm.
[0019] By adopting the above technical solution, the pore size and average particle size of the activated carbon are optimized, which helps to form tiny air channels inside the insole, promote air circulation in the shoe, reduce the feeling of stuffiness, improve the air permeability and moisture permeability of the EVA insole, and at the same time ensure the strength, softness and elasticity of the EVA insole.
[0020] Preferably, the porous silica and the activated carbon are pretreated by the following steps: Porous silica and activated carbon are added to a high-speed mixer, heated to 50-60°C, silane coupling agent is added and mixed evenly, heated and melted, added to porous silica, stirred and mixed, lubricant is added, and stirred evenly to obtain pretreated porous silica and activated carbon.
[0021] By adopting the above technical solution, porous silica and activated carbon can be evenly distributed in the EVA sole, increasing the channels inside the EVA insole, promoting air circulation inside the insole, and effectively reducing the stuffiness of the feet.
[0022] Among them, silane coupling agents can improve the interfacial bonding between porous silica, activated carbon and EVA, so that the two can be more firmly embedded in the EVA substrate, improving the strength of the EVA insole while maintaining its porous characteristics. Lubricants play a role in reducing friction between particles during the mixing process, allowing porous silica and activated carbon to be more evenly dispersed in the EVA substrate, helping to improve the softness and comfort of the insole and reducing performance defects caused by particle agglomeration.
[0023] Preferably, the number average molecular weight of the terminal epoxy polyether silicone oil is 5000-80000.
[0024] By adopting the above technical solution, by optimizing the number average molecular weight of the terminal epoxy polyether silicone oil, it can more effectively penetrate into the EVA substrate and interact with the EVA molecular chain, thereby improving the softness of the entire insole and making it more comfortable to wear. At the same time, the terminal epoxy polyether silicone oil interacts with the EVA molecular chain, which helps to form a more uniform and stable microporous structure inside the insole. These microporous structures can serve as channels for gas and moisture, promote air circulation and moisture discharge inside the insole, and thus improve the breathability of the insole.
[0025] Preferably, the number average molecular weight of the polyacrylamide is 1,000,000-1,500,000.
[0026] By adopting the above technical solution, the number average molecular weight of the polyacrylamide is optimized, which helps to enhance the overall strength and durability of the EVA insole. When used for a long time or subjected to external force, the insole is not easy to deform or break. At the same time, the polyacrylamide within the number average molecular weight range has good flexibility, which helps to form a good dispersion and combination in the EVA insole, thereby increasing the softness of the insole. When the insole is subjected to pressure, the polymer chain of the polyacrylamide can be deformed to a certain extent, absorb and disperse the pressure, and make the wearer feel more comfortable.
[0027] In a second aspect, the present application provides a method for preparing a soft and breathable EVA insole, using the following technical solution: A method for preparing a soft and breathable EVA insole comprises the following steps: S1, mixing ethylene-vinyl acetate copolymer, activated carbon, porous silica, chitosan, terminal epoxy polyether silicone oil, modified starch, cellulose and polyacrylamide to obtain a mixture; S2, extruding the mixture into granules and injection molding to obtain a soft and breathable EVA insole.
[0028] By adopting the above technical solution, the production process is simplified and the production efficiency is improved by extruding the mixture into granules and then injecting it into the mold. At the same time, the injection molding process can ensure the accuracy and consistency of the insole shape, which is conducive to the quality control of large-scale production.
[0029] In summary, this application has the following beneficial effects: 1. In the present application, ethylene-vinyl acetate copolymer, activated carbon, porous silica, chitosan, end-epoxy polyether silicone oil, modified starch, cellulose and polyacrylamide are used together to make the EVA insole have good air permeability and moisture removal, softness, elasticity, strength and durability, and can also show excellent softness, air permeability and moisture removal in high-intensity and high-humidity environments, which not only meets the needs of daily wear, but is also more suitable for high-intensity sports scenes such as mountaineering and long-distance running. DETAILED DESCRIPTION
[0030] Preparation Example Preparation Example 1 A modified starch is prepared by the following method: A: 40 g of polylactic acid and 100 g of solvent (butyl acetate) were mixed and stirred, and the temperature was raised to 75° C. until the polylactic acid was completely dissolved to obtain a polylactic acid solution; B: Stir 100g starch, 10g ammonium sulfate and 180g water, heat to 75°C, and stir until the starch becomes transparent to obtain gelatinized starch; C: Mix polylactic acid solution, gelatinized starch and 15 g of maleic anhydride, heat to 90°C, add 30 g of ammonium bisulfite solution dropwise, keep warm for 1 hour, then cool to 50°C, continue heating and stirring for 1 hour, add 10 g of 4-methylimidazole and stir until the temperature drops below 30°C, adjust the pH value to 7 with 30 g of aqueous ammonia to obtain modified starch.
[0031] The ammonium bisulfite solution is obtained by mixing ammonium bisulfite and water in a weight ratio of 1:4.
[0032] The difference between Preparation Example 2-3 and Preparation Example 1 is that the types, amounts and parameters of the raw materials used to prepare the modified starch are different. The specific differences are shown in Table 1: Table 1 Types, amounts and parameters of raw materials used in preparing modified starches in Preparation Examples 1-3 The ammonium bisulfite solution in Preparation Example 2 is obtained by mixing ammonium bisulfite and water in a weight ratio of 1:4.5.
[0033] The ammonium bisulfite solution in Preparation Example 3 is obtained by mixing ammonium bisulfite and water in a weight ratio of 1:5. Example
[0034] Ethylene-vinyl acetate copolymer was purchased from Dongguan Yunxin Plastic Raw Materials Co., Ltd. The brand is Japan Mitsui Chemicals and the grade is V961RC.
[0035] Commercially available modified starch was purchased from Wuhu Jinfenghe Biotechnology Co., Ltd. with the production number SC20161072300024.
[0036] Example 1 A soft and breathable EVA insole is prepared by the following method: S1, 400 g of ethylene-vinyl acetate copolymer, 80 g of activated carbon, 200 g of porous silica, 80 g of chitosan, 60 g of terminal epoxy polyether silicone oil, 90 g of commercially available modified starch, 60 g of cellulose and 30 g of polyacrylamide were mixed to obtain a mixture; S2, extruding the mixture into granules and injection molding to obtain a soft and breathable EVA insole.
[0037] The pore size of activated carbon is 50-60nm and the average particle size is 500-650nm.
[0038] The pore size of porous silica is 20-30 nm and the average particle size is 200-400 nm.
[0039] The number average molecular weight of the epoxy-terminated polyether silicone oil is 5,000.
[0040] The number average molecular weight of polyacrylamide is 1,000,000.
[0041] The difference between Example 2-3 and Example 1 is that the types, amounts and parameters of raw materials used to prepare the soft and breathable EVA insoles are different. The specific differences are shown in Table 2: Table 2 Types, amounts and parameters of raw materials used in preparing soft and breathable EVA insoles in Examples 1-3 Example 4 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the modified starch comes from preparation example 1.
[0042] Example 5 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the modified starch comes from preparation example 2.
[0043] Example 6 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the modified starch comes from preparation example 3.
[0044] Example 7 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the porous silica and activated carbon are pretreated by the following steps: Add 200 g of porous silica and 80 g of activated carbon into a high-speed mixer, heat to 50°C, add 2.8 g of silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) and mix evenly, heat and melt and add to the porous silica, stir and mix, then add 8.4 g of lubricant (fatty acid amide), stir evenly to obtain pretreated porous silica and activated carbon.
[0045] Example 8 A soft and breathable EVA insole. The difference between this embodiment and embodiment 4 is that the porous silica and activated carbon are pretreated by the following steps: Add 200 g of porous silica and 80 g of activated carbon into a high-speed mixer, heat to 60°C, add 2.8 g of silane coupling agent (acetyltrimethoxysilane) and mix evenly, heat and melt and add to the porous silica, stir and mix, then add 8.4 g of lubricant (castor oil), stir and mix evenly to obtain pretreated porous silica and activated carbon.
[0046] Example 9 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the average particle size of the porous silicon dioxide is 500-650nm.
[0047] Example 10 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the average particle size of the activated carbon is 200-400nm.
[0048] Embodiment 11 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polyacrylamide is 900,000.
[0049] Example 12 A soft and breathable EVA insole. The difference between this embodiment and embodiment 1 is that the number average molecular weight of the polyacrylamide is 2,000,000.
[0050] Comparative Example Comparative Example 1 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that zeolite powder is used instead of porous silica.
[0051] Comparative Example 2 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that zeolite powder is used instead of activated carbon.
[0052] Comparative Example 3 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that diatomaceous earth is used instead of chitosan.
[0053] Comparative Example 4 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that methyl silicone oil is used instead of terminal epoxy polyether silicone oil.
[0054] Methyl silicone oil was purchased from Jinan Yingyu Chemical Co., Ltd., model 201.
[0055] Comparative Example 5 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that starch is used instead of modified starch.
[0056] The starch is corn starch.
[0057] Comparative Example 6 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that stearic acid glyceryl is used instead of cellulose.
[0058] Comparative Example 7 A soft and breathable EVA insole. The difference between this comparative example and Example 1 is that polyethylene is used instead of polyacrylamide.
[0059] The molecular weight of polyethylene is 1,000,000.
[0060] Detection method / test method Rebound rate: The test adopts GT-7042-RE impact elasticity testing machine, cuts the soft breathable EVA insoles to be tested in the embodiment and comparative example into squares of 45mm*45mm, and measures their thickness, sets the pressure value to 50N, presses the pressure head to the surface of the EVA insole, releases the pressure, records the height of the shoe material after rebound, and calculates the rebound rate (%) = (height measured after the test - height before the test) / height before the test * 100%; Tear strength: tested according to GB / T10808-2006; Hygroscopicity: Referring to GB / T 1690-2010 standard, each material was immersed in water at 25°C, and the water absorption rate was measured after 24 hours. The higher the water absorption rate, the better the hygroscopicity. Air permeability test: The air permeability of the soft and breathable EVA insoles in the embodiment and the comparative example was tested using an air permeability tester. The test gas was nitrogen. The test time was 24 hours. The test pressure was 0.2 MPa. The greater the air permeability, the better the air permeability. The experimental data are shown in Table 3: Table 3 Experimental data of Examples 1-12 and Comparative Examples 1-7 By comparing Example 1 with Comparative Examples 1-7, the rebound rate, tear strength (except the tear strength of Comparative Example 7), hygroscopicity and air permeability of Comparative Examples 1-7 are all lower than those of Example 1, indicating that in the present application, by using ethylene-vinyl acetate copolymer, activated carbon, porous silica, chitosan, end-epoxy polyether silicone oil, modified starch, cellulose and polyacrylamide together, the rebound rate, tear strength, hygroscopicity and air permeability of the EVA insole can be effectively improved to meet the use requirements in high-intensity and high-humidity environments such as mountaineering and long-distance running.
[0061] Comparing Example 1 with Examples 4-6, the rebound rate, tear strength, hygroscopicity and air permeability of Examples 4-6 are all greater than those of Example 1, indicating that the modified starch prepared in the present application can effectively improve the rebound rate, tear strength, hygroscopicity and air permeability of the EVA insole.
[0062] Comparing Example 1 with Example 7, the resilience, tear strength, hygroscopicity and air permeability of Example 7 are all greater than those of Example 1; Comparing Example 4 with Example 8, the resilience, tear strength, hygroscopicity and air permeability of Example 8 are all greater than those of Example 4; It can be seen from Examples 1 and 7, and Examples 4 and 8 that pre-treating activated carbon and porous silica by the method of the present application is beneficial to improving the rebound rate, tear strength, moisture absorption and air permeability of the EVA insole.
[0063] Comparing Example 1 with Examples 9-10, the rebound rate, tear strength, hygroscopicity and air permeability of Examples 9-10 are all lower than those of Example 1, indicating that the rebound rate, tear strength, hygroscopicity and air permeability of the EVA insole can be effectively improved by optimizing the average particle size of the activated carbon and the average particle size of the porous silica.
[0064] Comparing Example 1 with Examples 11-12, the rebound rate, tear strength, hygroscopicity and air permeability of Examples 11-12 are all lower than those of Example 1, indicating that the rebound rate, tear strength, hygroscopicity and air permeability of the EVA insole can be effectively improved by optimizing the number average molecular weight of polyacrylamide.
[0065] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A soft and breathable EVA insole, characterized in that: Prepared from the following raw materials in weight percentage: Ethylene-vinyl acetate copolymer 40-52% Activated carbon 4-8% Porous silica 15-20% Chitosan 5-8% Epoxy-terminated polyether silicone oil 4-6% Modified starch 5-9% Cellulose 3-6% The remainder is polyacrylamide.
2. A soft and breathable EVA insole according to claim 1, characterized in that: The modified starch is prepared by the following method: A: Mix polylactic acid and solvent and stir, raise the temperature to 75-80°C until the polylactic acid is completely dissolved to obtain a polylactic acid solution; B: Stir starch, ammonium sulfate and water, heat to 75-80°C, and stir until the starch becomes transparent to obtain gelatinized starch; C: Mix polylactic acid solution, gelatinized starch and maleic anhydride, heat to 90-100°C, add ammonium bisulfite solution dropwise, keep warm for 1-2 hours after the addition is complete, then cool to 50-60°C, continue heating and stirring for 1-1.5 hours, add 4-methylimidazole and stir until the temperature drops below 40°C, adjust the pH value to 7-7.5 with ammonia water, and obtain modified starch.
3. A soft and breathable EVA insole according to claim 2, characterized in that: The weight parts of the raw materials used to prepare the modified starch are as follows: Polylactic acid 4-8 parts Solvent 10-15 parts 10-15 parts starch 1-2 parts ammonium sulfate 18-22 parts water Maleic anhydride 1.5-3 parts 3-4 parts of ammonium bisulfite solution 1-2 parts of methylimidazole; The ammonium bisulfite solution is obtained by mixing ammonium bisulfite and water in a weight ratio of 1:(4-5).
4. The soft and breathable EVA insole according to claim 1, characterized in that: The pore size of the porous silica is 20-50 nm, and the average particle size is 200-800 nm.
5. The soft and breathable EVA insole according to claim 1, characterized in that: The pore size of the activated carbon is 50-100 nm, and the average particle size is 500-900 nm.
6. The soft and breathable EVA insole according to claim 1, characterized in that: The porous silica and the activated carbon are pretreated by the following steps: Porous silica and activated carbon are added to a high-speed mixer, heated to 50-60° C., a silane coupling agent is added and mixed evenly, heated and melted, added to the porous silica, stirred and mixed, and then a lubricant is added and stirred evenly to obtain pretreated porous silica and activated carbon; wherein the weight of the silane coupling agent is 1% of the total weight of the porous silica and the activated carbon; and the weight of the lubricant is 3% of the total weight of the porous silica and the activated carbon.
7. The soft and breathable EVA insole according to claim 1, characterized in that: The cellulose is at least one of hydroxypropyl methylcellulose, carboxymethyl cellulose, carboxyethyl cellulose and lignocellulose.
8. The soft and breathable EVA insole according to claim 1, characterized in that: The number average molecular weight of the terminal epoxy polyether silicone oil is 5000-80000.
9. The soft and breathable EVA insole according to claim 1, characterized in that: The number average molecular weight of the polyacrylamide is 1,000,000-1,500,000.
10. A method for preparing a soft and breathable EVA insole as claimed in any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: S1, mixing ethylene-vinyl acetate copolymer, activated carbon, porous silica, chitosan, terminal epoxy polyether silicone oil, modified starch, cellulose and polyacrylamide to obtain a mixture; S2, extruding the mixture into granules and injection molding to obtain a soft and breathable EVA insole.
Citation Information
Patent Citations
Antibacterial breathable sole material and preparation method thereof
CN117586635A